POLÍTICAS PÚBLICAS NO ÂMBITO DO MINISTÉRIO DO ESPORTE E OS PLANOS PLURIANUAIS DOS GOVERNOS FERNANDO HENRIQUE CARDOSO, LUIZ INÁCIO LULA DA SILVA E DILMA ROUSSEFF: COM O ORÇAMENTO QUEM GANHA O QUÊ, QUANDO E COMO? - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This study aims to understand the Pluriannual Plans (PPA) on the periods of 2000-2003, 2004-2007, 2008-2011 and 2012 -2015, through resources allocation as well as decisions taken according to the budgetary priorities set by the Ministry of Sports or by any equivalent management body. This study addresses the issue by checking if the commitments assumed by the Federal Government achieved budget execution. This is a documentary, exploratory study of quantitative approach covering the Annual Budgetary Law Projects (PLOAs), the Annual Budget Laws (LOAs), the Pluriannual Plans (PPAs) and the Annual Evaluation Reports of the PPA, according to the proposed timeline. We concluded that primacy was given to high-performance sport only in the PPA 2012-2015. Even though such primacy was characterized by mega-events, these were not part of a historical sequence. Furthermore, we were able to infer that 2007 Pan-American Games served to redirect public policies of the Ministry of Sport towards high-performance sport.
Keywords: Políticas públicas; Esporte; Lazer; Ministério do Esporte; Public Policies; Sport; Recreation; Ministry of Sport; CNPQ::CIENCIAS SOCIAIS APLICADAS